Cenotic connection land biota Islands Western Antarctic - I. Dykyy; Y. Tsaryk; I. Shydlovskyy; V. Trokhymets; O. Holovachov (Ukrainian Antarctic Journal, 2012)
First studies have been conducted coenotic connections land biota West Antarctic islands and clarified their significance for the Antarctic tundra biogeocenoses, the material was collected during 11 and 14 Ukrainian Antarctic expeditions (2006-2007 and 2009-2010). Among coenotic connections land biota, was paid attention to fabrycal, forycal and biotopical connections. Found that representatives of avifauna such as Larus dominicanus, Phalacrocorax atriceps play an important role in the distribution of Deschampsia antarctica between the islands of the archipelago and colonization of territories gradually release from snowice cover under global warming. Study that the choice of material for nests of such species as L. dominicanus, Ph.atriceps, and Catharacta maccormicki show high plasticity (respectively 9, 8 and 5 fractions of material) and use most common in biogeocenoses materials. In particular, among the 5 species of mosses predominate (Sanionia georgico-uncinata, Pohlia nutans, Pohlia drummondii, Syntrichia princeps, Polytrichastrum alpinum); lichens – 1 species (Usnea аntarctica); algae – 3 species (Desmarestia chordalis, Plocamium cartilagineum, Cladodonta lyallii); terrestrial algae – 1 species (Prasiola crispa). Research that these species actively promote the formation of new habitat, Antarctic tundra. They carry with nesting material and soil invertebrate groups such as Collembola, Acarina, Chironomidae, Nematoda, Rotatoria and Tardigrada. In particular, Ph. atriceps creates favorable conditions for coexistence fauna of more than 10 species of soil invertebrates and distribute of 2 species plants; L. dominicanus – 10 species of invertebrates and the distribute of 3 species; C. maccormicki – 5 species of invertebrates. Analysis of the nesting material for the first time for archipelago Argentine Islands conducted showed that the nematode fauna is represented by more than 25 species 16 genera. Of these, eight are new to the fauna of Antarctica. Among soil nematodes dominated bacteriophages – 17 species, 4 species – mikrophages and phitophages, 3 – evryphages and predators or other unexplored. Through analysis of trophic, fabrycal, forycal and biotopical connections in biocenosis land archipelago, created their integrated model. It will develop the right mechanisms to maintain the Antarctic biota, in terms of sustainable development of the region the Argentine Islands.